Effect modification of consecutive high concentration days on the association between fine particulate matter and mortality: a multi-city study in Korea - Lim, Hyungryul; Bae, Sanghyuk; Choi, Jonghyuk; Choi, Kyung Hwa; Bae, Hyun Joo; Kim, Soontae; Ha, Mina; Kwon, Ho Jang (Epidemiology and Health, 2022)
OBJECTIVES: Although there is substantial evidence for the short-term effect of fine particulate matter (PM2.5) on daily mortality, few epidemiological studies have explored the effect of prolonged continuous exposure to high concentrations of PM2.5. This study investigated how the magnitude of the mortality effect of PM2.5 exposure is modified by persistent exposure to high PM2.5 concentrations. METHODS: We analyzed data on the daily mortality count, simulated daily PM2.5 level, mean daily temperature, and relative humidity level from 7 metropolitan cities from 2006 to 2019. Generalized additive models (GAMs) with quasi-Poisson distribution and random-effects meta-analyses were used to pool city-specific effects. To investigate the effect modification of continuous exposure to prolonged high concentrations, we applied categorical consecutive-day variables to the GAMs as effect modification terms for PM2.5. RESULTS: The mortality risk increased by 0.33% (95% confidence interval [CI], 0.16 to 0.50), 0.47% (95% CI, -0.09 to 1.04), and 0.26% (95% CI, -0.08 to 0.60) for all-cause, respiratory, and cardiovascular diseases, respectively, with a 10 μg/m3 increase in PM2.5 concentration. The risk of all-cause mortality per 10 μg/m3 increase in PM2.5 on the first and fourth consecutive days significantly increased by 0.63% (95% CI, 0.20 to 1.06) and 0.36% (95% CI, 0.01 to 0.70), respectively. CONCLUSIONS: We found increased risks of all-cause, respiratory, and cardiovascular mortality related to daily PM2.5 exposure on the day when exposure to high PM2.5 concentrations began and when exposure persisted for more than 4 days with concentrations of ≥ 35 μg/m3. Persistently high PM2.5 exposure had a stronger effect on seniors.
Keywords: Air Pollution; Cardiovascular Diseases; China; Cities; Environmental Exposure; Humans; Mortality; Particulate Matter; Temperature; Air pollution; Epidemiology; Mortality; Particulate matter; Time-series analysis